The Afropolitan Identity as a Rhizome - Okwudiri Anasiudu (Hasanuddin University, 2021)
Working within the tenets of Selasi and Mbembe’s notion of Afropolitanism and Guatarri and Deleuze (1987) concept of a rhizome, this paper interrogates and contextualises the Afropolitan identity as a rhizome. The aim is to deepen the conversation and debate on Afropolitanism as a new way of mapping the African cultural identity in synch with the world at large, while offering a new descriptive vocabulary for it. The examples interrogated in this study are drawn from selected African novels which evince the Afropolitan sensibilities. This is portrayed through rhizomatic characterisation. This study is also in conversation with Ede’s notion of